Kesesuaian Jenis Pohon Berdasarkan Karakteristik Lahan di Lembang Simbuang Kabupaten Tana Toraja, Indonesia - Budirman Bachtiar; Suhartati Suhartati; Resti Ura' (Universitas Hasanuddin, 2022)
The suitability of the types of trees planted through the forest and land rehabilitation program in Simbuang District, Tana Toraja Regency, is assessed based on land characteristics. Evaluation of the suitability of tree species is carried out to determine the potential of tree species Coffea arabica, Gymnostoma rumphianum, Paraserianthes falcataria, Gliricidia sepium, and Artocarpus heterophyllus can be developed as forest and land rehabilitation plants in Simbuang District. This research was conducted through two stages, namely the field observation stage and laboratory analysis. Evaluation of land suitability is carried out using the matching method (Matching) between land characteristic data and the criteria for planting plant needs, land characteristics data are tabulated based on land suitability parameters, namely S1 (very precise), S2 (sufficiently appropriate), S3 (marginal according to), N (not appropriate) and their limiting factors. The results showed that the characteristics of the land and the suitability of tree species in the forest area SimbuangDistrict of Tana Toraja Regency have the same characteristics where the types of trees that can be developed S2 (quite appropriate) to be developed are Coffea arabica, Gymnostoma rumphianum, Paraserianthes falcataria, Gliricidia sepium Mangifera indica, and Artocarpus heterophyllus. The potential land balance for mangoes is S3 (marginal appropriate) with the limiting factors being the annual average temperature, the number of dry months, and the annual rainfall.